Development of Web-Based Library Management System for SMA Negeri 13 Surabaya (PUSGALAS) - Kristanto, Titus; Kamali, Muhammad Adib (Abdi Masyarakat, 2025)
School libraries are one of the important facilities that can be used to improve literacy culture and learning quality. However, managing libraries manually often causes various problems, including problems with recording book data, borrowing transactions, and limited access to information for students and teachers. Community service activities in the form of building a web-based library management system called PUSGALAS (Pusat Galeri Literasi SMA Negeri 13 Surabaya). The purpose of the system is to improve efficiency and ease of access to literacy services in schools. Needs analysis, design, implementation, testing, and evaluation are part of the Waterfall model used in the development of this system. This system is built using the PHP programming language and utilizes the Laravel framework and MySQL database. Book collection management, borrowing and returning, book searching, digital shelf visualization, and statistical reports are the main features available. The test results showed that the system was well received by users and met functional needs, with a satisfaction rate of more than 90% based on the User Acceptance Testing (UAT) evaluation. Therefore, PUSGALAS is considered effective in helping the transformation of school libraries into digital and can be an innovative solution to improve literacy services in secondary schools.